(untitled) (Architecture Image Studies, 2023)
As society faces a range of pressing issues including climate change, social inequality, and economic instability, organizations known as social enterprises are emerging to address these challenges. These organizations not only aim to generate profits but also to create positive economic, environmental, individual, community and social values. A local example, Fixers’ Club (Onaranlar Kulübü), aims to increase dialogue between the city, the environment, and the people through placemaking projects in Turkey. However, unlike many urban place-making social initiatives and organizations, the club has assertive flexibility regarding actors and roles in their projects - which makes them peculiar. In this light, this paper aims to explore and understand dynamics, actors and roles in various scaled social utility urban place-making. To achieve this we focus on three cases by Fixers’ Club. As a result, it is seen that the number of actors and their roles varies significantly according to the scale of the projects which indicates the club’s flexible approach. Also, even though the core team carries out the preparation phases of the projects, actors in the design and implementation phases are mostly outsiders with various expertises.